Penerapan Pembelajaran Outdoor dengan Pendekatan Saintifik untuk Meningkatkan Hasil Belajar Siswa SMPN 6 Kota Bengkulu - Rahyuni Rahyuni; Zamzaili Zamzaili; Aceng Ruyani (PendIPA Journal of Science Education, 2018)
[Implementation of outdoor learning with saintific approach to improve student learning of SMPN 6 Bengkulu City]. The aims of this study was to know the results of scientific learning (outdoor) and see the comparison the value of students’s group who learn by using outdoor learning and groups of students who do not use outdoor learning. The subject of this research is the students of class VII SMPN6 Bengkulu City on academic year 2016/2017. The sample who taken are class VII G class control class VII H, experimental class, class VII E as a testing class. Sampling technique by purposive sampling. Instrument used double choice test instrument 25 problem,. The technique of data analysis using statistic Anova Mix (mixed Anova). Test normality by using test of covariance matrix. The average value of pretest of the experimental class students 62.1 after the average treatment of student postes increased to 86.25 which means an increase of 24.15. The control class Pretest and postes results Average score of pretest students 65,9 after conventional learning average student postes score increased to 75,5 which means an increase of 9.6. Student learning outcomes using outdoor learning method is higher than those not using the method, it is seen from the average experimental class value (80,75) bigger than control class (64,00) with increase of 26,37%.    Keywords: Outdoor learning; saintific approach; student learning outcomes.